Age-Related Whole-Brain Structural Changes in Relation to Cardiovascular Risks Across the Adult Age Spectrum - Gu, Tao; Fu, Chunyi; Shen, Zhengyin; Guo, Hui; Zou, Meicun; Chen, Min; Rockwood, Kenneth; Song, Xiaowei (Frontiers in Aging Neuroscience, 2019)
Background: The brain atrophy and lesion index (BALI) has been developed to assess whole-brain structural deficits that are commonly seen on MRI in aging. It is unclear whether such changes can be detected at younger ages and how they might relate to other exposures. Here, we investigate how BALI scores, and the subcategories that make the total score, compare across adulthood and whether they are related to the level of cardiovascular risks, in both young and old adulthood. Methods: Data were from 229 subjects (72% men; 24-80 years of age) whose annual health evaluation included a routine anatomical magnetic resonance imaging (MRI) examination. A brain atrophy and lesion index (BALI) score was generated for each subject from T2-weighted MRI. Differences in the BALI total score and categorical subscores were examined by age and by the level of cardiovascular risk factors (CVRF). Regression analysis was used to evaluate relationships between continuous variables. Relative risk ratios (RRR) of CVRF on BALI were examined using a multinomial logistic regression. The area under the receiver operating characteristic curve was used to estimate the classification accuracy. Results: Nearly 90% of the participants had at least one CVRF. Mean CVRF scores increased with age (slope=0.03; r=0.36, 95% confidence intervals: 0.23-0.48; p<0.001). The BALI total score was closely related to age (slope=0.18; r=0.69, 95% confidence intervals: 0.59-0.78; p<0.001), as so were the categorical subscores (r’s= 0.41-0.61, p<0.001); each differed by the number of CVRF (t-test: 4.16-14.83, Chi2: 6.9-43.9, p’s<0.050). Multivariate analyses adjusted for age and sex suggested an independent impact of age and the CVRF on the BALI score (for each year of advanced age, RRR=1.20, 95% CI= 1.11-1.29; for each additional CVRF, RRR=3.63, 95% CI=2.12-6.23). The CVRF and BALI association remained significant even in younger adults. Conclusion: The accumulation of MRI-detectable structural brain deficits can be evident from young adulthood. Age and the number of CVFR are independently associated with BALI score. Further research is needed to understand the extent to which other age-related health deficits can increase the risk of abnormalities in brain structure and function, and how these, with BALI scores relate to cognition.